Dilema Penyerahan Tanah Ulayat - Indrizal, Edi; Ermayanti, Ermayanti; Irwandi, Ade (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This paper aims to explain the dilemma of handing over customary land for oil palm plantations in Nagari Kinali. This study uses a descriptive qualitative approach with data collection through in-depth interviews and literature studies. The results of the study show that there is dualism between the holders of the Tuanku Kinali title as leaders of the customary area in Nagari Kinali. As a result, internal conflicts between them occur. Additionally, conflicts with companies arise due to the lack of transparency in the distribution of plasma and plasma management. This has become a dilemma for the community. On the one hand, they conflict with Ninik Mamak, and on the other hand, they must resist companies taking away their rights. Therefore, this is inseparable from the influence of capitalism, which is marked by an increasing trend of commercialization and monetization that has penetrated the very fabric of traditional rural communities. Keyword: Customary Land, Dilemma, Handover, Kinali.